Empathic behavior in nursing and medicine students - Pertuz Meza, Yolima; Reyes Ríos, Luz Angela; Gamarra-Moncayo, José; Reyes-Reyes, Fernando; Reyes-Reyes, Alejandro; Díaz-Narváez, Víctor (Revista Cuidarte, 2024)
Highlights• Empathy not only allows for more humane care of patients, but also and partially determines the effectiveness and success of treatments.• A psychometric study of empathy assessment instruments is always required before estimating empathy levels or empathy dimensions.• Longer educational programs, such as medicine, may give students more time for clinical exposure, personal development, and emotional maturation.• Curriculum and educational environment play an important role in developing empathy in health science students.Introduction: Empathy is an attribute that contributes to humane care of patients and increases the likelihood of successful treatment. Objectives: To measure the levels of empathy and its dimensions, and diagnose empathic behavior in medicine and nursing students. Materials and Methods: This was a non-experimental, cross-sectional study in which Colombian nursing and medicine students were evaluated using the Jefferson Scale of Empathy (JSE). A factor analysis, an analysis of invariance, and a two-way analysis of variance (ANOVA) were used, and the data were compared to specific cut-off points for each program. Effect size and power of the tests were estimated for the comparisons performed. Results: The theoretical model for the construct ‘empathy’ fitted the observed data, and the invariance of the model between groups was confirmed. Differences were observed between nursing and medical students, as well as between sexes, with results favoring the women group. Discussion: The differences found between students could be partly due to the curricular differences of the programs and the students' interests, whereas those related to sex may be due to characteristics observed in Latin American population. The identified empathy deficiencies allowed for the development of a diagnosis for nursing and medicine students. Conclusion:  Based on the findings, it is possible to diagnose the empathy levels of students of both programs by identifying the deficiencies observed in the dimensions of empathy.How to cite this article: Pertuz Meza Yolima, Reyes Ríos Luz Angela, Gamarra-Moncayo José, Reyes-Reyes Fernando, Reyes-Reyes Alejandro, Díaz-Narváez Víctor. Empathic Behavior in Nursing and Medicine Students. Revista Cuidarte. 2024;15(3):e4007.  https://doi.org/10.15649/cuidarte.4007
Keywords: Empathy; Medicine; Nursing; Student; Psychometry